find :
2y + 5x ÷3y - 5x= 5÷2
(i) X:Y
(ii) x, if y = 70
(iii) y, if x = 33
Answers
Answered by
6
Answer:
hope, it will help you
Step-by-step explanation:
(i) (2y + 5x)/(3y – 5x) = (2 × 2 + 1)/2
(2y + 5x )/(3y – 5x) = 5/2
⇒ 2(2y + 5x) = 5 × (3y – 5x)
⇒ 4y + 10x = 15y – 25x
⇒ 35x = 11y
⇒ x/y = 11/35 i.e. x : y = 11 : 35
(ii) (2y + 5x)/(3y – 5x) = 5/2
Given y = 70
(2 × 70 + 5x)/(3 × 70 – 5x) = 5/2 ⇒ (140 + 5x)/(210 – 5x) = 5/2
⇒ 2 × (140 + 5x) = 5 × (210 – 5x)
⇒ 280 + 10x = 1050 – 25x
⇒ 35x = 1050 – 280
⇒ 35x = 770 ⇒ x = 770/35 = 22
(iii) (2y + 5x)/(3y – 5x) = 5/2
Given x = 33
(2y + 5 × 33)/(3y – 5 × 33) = 5/2 ⇒ (2y + 165)/(3y – 165) = 5/2
⇒ 2 × (2y + 165) = 5 × (3y – 165)
⇒ 4y + 330 = 15y – 825
⇒ 11y = 1155
⇒ y = 1155/11 = 105
Similar questions